Tinjauan Wakaf Saham Hak Atas Kekayaan Intelektual dalam Perspektif Hukum Islam - Khaerul Aqbar; Sulkifli Herman; Arsan Arsan (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, Indonesia, 2022)
This study aims to determine and understand the law of stock waqf in the perspective of Islamic law, the problems that the researcher raises in this thesis are; First, how is the implementation of IPR share waqf in Indonesia. Second, how is waqf of IPR shares in the perspective of Islamic law. This research uses descriptive qualitative research (non-statistical), using library research method (library review) and using normative and juridical normative approaches. The research results found are as follows; First, the implementation of IPR Shares Waqf in Indonesia is different from the waqf of immovable assets in the form of land or buildings because it must fulfill the eternal aspects and the form of shares that cannot be used directly. There are two models of stock waqf launched by the Indonesia Stock Exchange (IDX). The first is waqf which is sourced from the profits of IPR stock investors and the second is waqf which makes IPR shares the object of waqf. The application of waqf is carried out by the wakif to nadzir in the presence of the Waqf Pledge Deed Official (PPAIW) witnessed by 2 (two) witnesses and stated orally and or in writing which is the will of the wakif and stated in the waqf pledge deed by PPAIW. Second, the Islamic legal perspective on waqf of intellectual property rights if it refers to the Hanafi, Syafi'i and Hanbali schools, then IPR shares cannot be waqf because they do not have a material form. However, if you take the opinion of the Maliki School, then IPR shares can be waqf, because the Maliki School states that the object of waqf does not have to be a material object (tangible) but can also be an immaterial object (intangible). And if you look at the legislation and the decisions of the Indonesian Ulema Council (MUI) then IPR shares can be waqf, considering the value and benefits are not small.